Beyond 2D: effects of photobiomodulation in 3D tissue-like systems - Bikmulina, Polina Y. (J Biomed Opt, 2020)
Significance: Currently, various scaffolds with immobilized cells are widely used in tissue engineering and regenerative medicine. However, the physiological activity and cell viability in such constructs might be impaired due to a lack of oxygen and nutrients. Photobiomodulation (PBM) is a promising method of preconditioning cells to increase their metabolic activity and to activate proliferation or differentiation. Aim: Investigation of the potential of PBM for stimulation of cell activities in hydrogels. Approach: Mesenchymal stromal cells (MSCs) isolated from human gingival mucosa were encapsulated in modified fibrin hydrogels with different thicknesses and concentrations. Constructs with cells were subjected to a single-time exposure to red (630 nm) and near-infrared (IR) (840 nm) low-intensity irradiation. After 3 days of cultivation, the viability and physiological activity of the cells were analyzed using confocal microscopy and a set of classical tests for cytotoxicity. Results: The cell viability in fibrin hydrogels depended both on the thickness of the hydrogels and the concentration of gel-forming proteins. The PBM was able to improve cell viability in hydrogels. The most pronounced effect was achieved with near-IR irradiation at the 840-nm wavelength. Conclusions: PBM using near-IR light can be applied for stimulation of MSCs metabolism and proliferation in hydrogel-based constructs with thicknesses up to 3 mm.